Treatment of an expansive soil by mechanical and chemical techniques. Issue 3 (1st June 2014) - Estabragh, A.R.; Rafatjo, H.; Javadi, A.A.
Abstract : ABSTRACT: This paper presents the results of treatment of an expansive soil by mechanical and chemical techniques against swelling. Mechanical treatment was done by reinforcing the soil with randomly distributed fibres and chemical treatment by using cement or lime as a chemical agent. All the experiments on untreated and treated samples were conducted in an oedometer. The experimental programme consisted of two groups of tests. The first group involved the tests on expansive soil reinforced with randomly distributed fibres (mechanical improvement) with different percentages (0.5, 1 and 1.5%), and different lengths (10, 20 and 30 mm), in bar shape with diameter of 0.30 mm or tape shape with two different widths (3.0 and 5.0 mm). The second group of tests consisted of samples that were mixed with different percentages (5, 8 and 10%) of cement or lime (chemical improvement) for different curing times. The results showed that, compared with the natural soil, the swelling behaviour (swelling potential and swelling pressure) was reduced by adding randomly mixed discrete fibres. The reduction of swelling potential and swelling pressure is also a function of percentage, length and type of fibre (bar or tape shape). The results also indicated that the addition of cement and lime caused reduction in swelling potential and its effect was considerably more than the influence of fibre. The effect of chemical agent is also a function of percentage of the chemical agent and the curing time.